Omnipotence and its Limits. Comments on the Concept of Omnipotence of Ryszard Kleszcz - Mordarski, Ryszard (Analiza, racjonalność, filozofia religii: Księga jubileuszowa dedykowana Profesorowi Ryszardowi Kleszczowi. Nr 6 (2020), 2020)
Ryszard Kleszcz presents an interesting interpretation of God’s omnipotence, which arises from a strong concept of rationalism, which has its genesis in the program of the Lvov-Warsaw School. This concept concerns the logical and moral problems of omnipotence, addresses the paradoxes of omnipotence and the possibility of changing the past by an omnipotent being. In the text, I subject this concept to a critical analysis to show further possibilities in interpretation, which enables Kleszcz’s understanding of omnipotence.